The Analysis of the Second Pillar Pension Funds and the Role of Expectations - Bartkus, Algirdas (Organizations and Markets in Emerging Economies, 2014)
This paper continues the analysis of the second pillar pension funds and is based on the results that were published in June 2013 in the journal “Organizations and Markets in Emerging Economies”, under the title “On Future Pensions from the Second Pillar Pension Funds”. The results of the previously published study that one needs to keep in mind for the full perception of the material are also presented here. The main result of this paper is interpretation and exhaustive quantitative analysis of cointegrating relationship among social insurance contributions transferred into the second pillar pension funds and assets value of these funds. More specifically, this paper explains what is represented by the equilibrium error and submits a mathematical model under rational expectations with detailed comments.